Poco Loco - Krause, J. R. (Amazon Children's Publishing, 2013)
"Meet Poco Loco. He's a very unusual ratón. He likes to invent wacky things. When Poco Loco's Waffle Iron-Weather Forecaster predicts mal tiempo, Poco Loco runs to tell his barnyard friends. But it's still sunny out, and the other animals don't believe him. Then a roar of wind whips through their picnic, and Poco Loco and his friends fly up, up, and away. But never fear! Poco Loco will use his wits (and one crazy invention) to save the day!"--P. [4] of cover.